Non-rubber modified impact polystyrene by suspension polymerization : Bench scale studies - Khan H U; Bhattacharyya K K; Goel P K; Gupta V K; Wadhera B M L (Journal of Applied Polymer Science, 1996)
Polystyrene (PS) homopolymer is transparent but has low impact strength. High impact PS (HIPS), made by grafting on elastomer, has good impact strength but is not transparent. The operating parameters, namely, polymerization temperature and initiator concentration, during styrene homopolymerization (in suspention) can be modified such that 5-10;of benzene-insoluble PS gel is formed that remains dispersed as very fine to small discrete particles in the continuous PS phase. The resulting polymer retains transparency and impact properties comparable to those of HIPS.
Keywords: Polymerization; Polystyrene